Implementasi Pendidikan Karakter dalam Pembentukan Kepribadian Anak Didik di SDN 82 Dante Koa Kecamatan Baraka - Awis, Awis (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The purpose of this study was to find out: The application of character education in developing the personality of students at SDN 82 Dante Koa, Baraka District. This research is an exploratory qualitative research using data collection techniques obtained from researchers in the wild. In research, phenomena are interpreted in terms that can be understood by informants. The results of this study are: 1) the application of character education in shaping students' personalities, namely every Monday, teaching children to carry out ceremonies, field cleaning programs, class pickets, encouraging students to take trash to its place. separation of organic and inorganic, students must arrive at school every morning at 07.15, students are required to read prayers every time, during and at the end of learning, students are encouraged to do good deeds every Friday, students every Saturday before entering the first hour. class, students work together, both ends and involve students in learning, they shake hands with the teacher, the school canteen also has an honor canteen, and besides that, students sing after finishing studying. obligatory song 2) Factors that inhibit and support the personality development of students at SDN 82 Dante Koa Baraka Regency, namely some parents do not fully participate in the introduction of character values ​​given to them by the school, parents do not fully control them. children's pupils waiting for school, adaptation at home does not match adaptation to school, unsupportive social environment. However, SDN 82 Dante Koa, Baraka Regency is a supporter of the formation of student personality, on behalf of the family, environment and school as well as collaboration between school and parents. 3) the efforts of the principal and teacher in shaping the personality of the students of SDN 82 Dante Koa, Baraka District, namely the teacher must be good at maintaining attitudes during learning.